Liquid-exfoliated molybdenum telluride nanosheets with superior electrocatalytic hydrogen evolution performances. Issue 17 (1st December 2018) - Qiao, Hui; Huang, Zongyu; Liu, Shengqian; Liu, Yundan; Li, Jun; Qi, Xiang
Abstract: Molybdenum Telluride (MoTe2 ) is widely used in the field of optoelectronics because of its excellent electron mobility and good environmental stability. Recent advances have shown that the reduction in the thickness of two-dimensional (2D) layered materials allows for greater surface area and more active sites to enhance electrocatalytic performance. Here, we prepared MoTe2 nanosheets by liquid exfoliation. Characterization of the morphology and lattice structure of MoTe2 nanosheets by a series of characterization methods. A three-electrode electrochemical system test results demonstrated that the MoTe2 nanosheets have excellent electrocatalytic activity and stability in H2 SO4 solution compared to bulk MoTe2. In addition, the MoTe2 nanosheets also exhibited optimal electrocatalytic properties for hydrogen evolution reaction (HER) with −309 mV overpotential at a current density of 10 mA/cm 2 and a low Tafel slope of 118.9 mV/dec in a 0.5 mol/L (M) H2 SO4 solution. Our work demonstrates that MoTe2 nanosheets have good prospects for use in electrocatalytic devices as high-performance electrocatalysts.